Sustainable reuse of waste glass and incinerated sewage sludge ash in insulating building products: Functional and durability assessment. (1st November 2019) - Lu, Jian-Xin; Zhou, Yifan; He, Pingping; Wang, Shengnan; Shen, Peiliang; Poon, Chi Sun
Abstract: Using thermal insulating materials for internal walls construction is an effective way for improving the energy-saving of buildings. This study reports the development a green concrete partition wall block using recycled glass as aggregates and incinerated sewage sludge ash (ISSA) as a partial replacement of Portland cement. Functional (density, porosity, compressive strength, thermal conductivity) and durability (drying shrinkage, fire resistance) performances were assessed. The experimental results showed that the eco-friendly blocks had sufficiently high strength to serve as a building partition material. Furthermore, the densities of the blocks were reduced with the incorporation of the glass aggregates and ISSA. Encouragingly, the combined use of glass aggregates and ISSA significantly reduced the drying shrinkage of the partition blocks. In terms of thermal insulation, the thermal conductivity of the blocks decreased considerably when the recycled glass and the ISSA were utilized simultaneously. Especially, the fire resistance of the partition blocks was improved effectively when the glass aggregates were used to totally replace the fine aggregates. Based on the findings, joint applications of waste glass and ISSA in producing partition wall blocks are appealing as it not only provides an alternative approach to reuse the wastes, but also achieve superior performance as an insulating wall material. Graphical abstract: Image 102206 Highlights: A novel insulating partition wall block prepared with waste materials is developed. Combined use of waste glass and incinerated sewage sludge ash in partition block is feasible. The sustainable partition wall block has low drying shrinkage and low thermal conductivity. The developed partition wall block has superior strength and excellent fire resistance.